The relationship between forest fire and deforestation in the southeast Atlantic rainforest - de Praga Baião, Cheila Flávia [UNESP]; Santos, Fabrícia Cristina [UNESP]; Ferreira, Marcos Paulo [UNESP]; Bignotto, Rafael Beltrame; da Silva, Rafael Felipe Guatura [UNESP]; Massi, Klécia Gili [UNESP] (Public Library of Science (PLoS), 2023)
Given the scarcity of studies relating fire to deforestation in the Atlantic Forest and great economic and ecological importances of this biome, this work aimed to investigate this relationship in the Atlantic Forest of the State of São Paulo, trying to answer whether deforestation is related to fire events in up to three years, if there are regions most affected by this relationship and what land use and land cover predominates after fire and deforestation in these areas. The study was carried out in Evergreen Forest and Semideciduous Seasonal, along the time series from 2000 to 2019 using the MapBiomas Project database to survey deforested and burned sites with moderate to high severity fires. Burning positively influenced deforestation in EGF in eight of 19 years studied (2001, 2004, 2005, 2007, 2008 and 2009, 2013 and 2015), while only for three years in the SSF. Burning followed by deforestation corresponded to only 3.2% of the total deforestation, located mainly in the eastern region of the state with the highest density in the EGF. Most of these areas have been converted to agriculture. This study provides the first indication that, generally, fire is not a driver of deforestation in the southeast Atlantic Forest